As artes visuais e os centros de inovação universitários: estudo de caso CI e LabCriativo UNIPÊ-PB - Méro, Isis Amaral (2021)
This is a qualitative research on the relationship between the visual arts and university innovation centers, with a case study developed at the Innovation Center (CI) and Innovation (NI) LabCriativo at Centro Universitário UNIPÊ, located in the city of João Pessoa, state of Paraíba. Its general objective is to analyze the relevance of visual arts in university innovation centers and for specific objectives: to analyze concepts, methodologies and guidelines in those centers; study innovative approaches and practices in art, education and technology and investigate the applicability of visual arts at CI and LabCriativo UNIPÊ PB. The theme is inserted in the scenario of growth of the creative economy in the state of Paraíba, through recognition of the municipality of João Pessoa as a creative nucleus by UNESCO and the promotion of academic production through research in the area of innovation and new technologies, as well as growth worldwide and regional investment in the creation of university technology and innovation centers, which makes the studied scenario suitable for investigations on the importance of visual arts in the midst of innovation. We started this research by studying university innovation centers, where we analyzed the emergence and expansion of innovation centers in the FABLAB network, the innovation centers in the state of Paraíba, the project management methodology and the interdisciplinary processes of building and disseminating knowledge academic. Innovative centers in art, education and technology were studied, such as (CI) BAUHAUS and studios, (NI) Stúdio Taliesen West, (NI) Stúdio The factory and (NI) Stúdio Olafur Eliasson, as well as concepts and productions innovative in multisensory art and technology, ephemeral art and architecture, design thinking methodology and technology in parametric design. We believe that this research can serve as a basis for the greater insertion of visual arts in the referred innovation centers studied and as a source for other research on the subject.